Let's simplify the expression step-by-step:
\[ -9.2(8x - 4) + 0.7(2 + 6.3x) \]
First, distribute \(-9.2\) and \(0.7\) into their respective parentheses:
- \( -9.2(8x) = -73.6x\)
- \( -9.2(-4) = 36.8\)
- \( 0.7(2) = 1.4\)
- \( 0.7(6.3x) = 4.41x\)
Now, combine the results:
\[ -73.6x + 36.8 + 1.4 + 4.41x \]
Combine like terms:
-
For the \(x\) terms: \(-73.6x + 4.41x = -69.19x\)
-
For the constant terms: \(36.8 + 1.4 = 38.2\)
So, combining all together gives:
\[ -69.19x + 38.2 \]
Thus, the simplified expression is:
\[ \boxed{-69.19x + 38.2} \]